2013
DOI: 10.3748/wjg.v19.i25.3918
|View full text |Cite
|
Sign up to set email alerts
|

Caustic injury of the upper gastrointestinal tract: A comprehensive review

Abstract: Prevention has a paramount role in reducing the incidence of corrosive ingestion especially in children, yet this goal is far from being reached in developing countries, where such injuries are largely unreported and their true prevalence simply cannot be extrapolated from random articles or personal experience. The specific pathophysiologic mechanisms are becoming better understood and may have a role in the future management and prevention of long-term consequences, such as esophageal strictures. Whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
465
4
49

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(526 citation statements)
references
References 131 publications
8
465
4
49
Order By: Relevance
“…Patients with grade 1 or 2A injury are permitted oral intake earlier and are generally discharged within days with antacid therapy. Patients with grade 2 or 3 injury however, are more severe cases and may need closer observation and may stay longer in hospital [2]. In the current study, the endoscopic findings of 28 patients (23.5%) were normal and most of the patients (42/119) had gastric involvement.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Patients with grade 1 or 2A injury are permitted oral intake earlier and are generally discharged within days with antacid therapy. Patients with grade 2 or 3 injury however, are more severe cases and may need closer observation and may stay longer in hospital [2]. In the current study, the endoscopic findings of 28 patients (23.5%) were normal and most of the patients (42/119) had gastric involvement.…”
Section: Discussionmentioning
confidence: 70%
“…Betalli et al reported that the presence of symptoms was the strongest predictor of severe esophageal lesions in a multi-centre observational study of a pediatric population [18]. Endoscopy is usually recommended in the first 12-48 hours after caustic ingestion [2] and is reliable for up to 96 hours after the injury [17]. The degree of injury determined on endoscopy is the major finding for patient management and prediction of complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researches mentioned it's safe to repeat endoscopy up to 3 weeks after caustic injury in expert hands [13,14]. Although upper gastrointestinal series plays the role in clinical evaluation, it's not as precise as endoscopic examination.…”
Section: Introductionmentioning
confidence: 99%